ПРОБЛЕМИ ТА ПЕРСПЕКТИВИ ПУБЛІЧНОЇ ПОЛІТИКИ У СФЕРІ СОЦІАЛЬНОГО ЗАХИСТУ ПОЛІЦЕЙСЬКИХ - Kravchenko, Milena; Beglaryan, Olena (Zhytomyr Ivan Franko State University, 2023)
Public policy as regards the police officers social protection is a purposeful and organized activity of public administration subjects, which in the process of exercising their powers through a set of administrative, legal, economic, and social measures contributes to the development of both short- and long-term programs of social protection of the police officers in order to protect their rights and legitimate interests in accordance with the conditions of service, status of the person and their family members during service and upon its completion. Following the analysis of the international experience of social protection of police officers and taking into account the current situation in Ukraine, we can conclude the national police staff members do not enjoy the high level of social security. This leads, above all, to improper performance by police officers of their professional duties, as well as to corruption risks, a negative phenomenon in society, which cancels out the implementation of reforms and development of the State in all areas. In this regard, there is an urgent need to review the existing legislation on social security for compliance both with international standards, and with current national legal and economic circumstances. In particular, we are talking about decent financial support, provision of free housing on lease at the expense of budget funds, introduction of decent monetary compensation for participation in military operations, payment of one-time allowance, etc. At the same time, due to the lack of a significant part of budget allocations, the issue of financing the social security of the police officers in Ukraine remains critical, in particular in terms ofpolice officers’ pensions and the provision of insurance benefits due to disability or death of a police officer while on duty. The article offers real steps to specific qualitative changes to be implemented without delay. After all, today police officers protect the rights and freedoms of citizens. Today they need an independent social protection and confidence in the future.